Avaliação do comportamento da fundação de barragem em Rocha Arenítica: estudo de caso da Barragem Jaburu I - Sousa, Lucrécia Nogueira de (2014)
The foundation of the Jaburu I dam it is a classical performance case of foundations in sandstone sedimentary rock. The continuous monitoring of the dam has been the detected the non-regular seepages and adopted in establishing the planning and execution of the remediation campaigns in way to keep the foundation and dam’s structures in safety conditions over three decades of operation, in despite of the ineffectiveness of conventional treatment foundation in sedimentary formation that had been used. Seepage anomalies indentified since the first filling of the reservoir in some regions of embankment and its foundation, detaching a significant flow in the left abutment which reached the maxima discharge of 47 l / s in 1988. Since then new points of resurgences have been identified and monitored by flow gages located in the downstream region. This monograph presents the events recorded in the flow gages and the remedial campaigns adopted to reduce the seepage in the foundation, embankment and abutments of the dam, as well as others specific interventions designed to recover the internal drain, stabilize the dam and to fill the cavities formed by the decomposition of the sandstone rock in the foundation. After the publication of the Law 12.334/2010, which established the National Policy of Dam Safety, it was established a complete list of responsibilities related to the safety of dams in Brazil, some of them already taken as routine by the Government of Ceará since 2002. This monograph recommends to the rock foundations of the dam, treatments with new sealing technologies that would mitigate the present anomalies.